Relationship Between Screen Time and Physical Activity Among Adolescents Across the COVID-19 Pandemic - Aisya Yafis Iqlima; Karuniawaty, Titi Pambudi; Wiguna, Putu Aditya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The Covid-19 pandemic has caused changes in various aspects. The government's policy in order to suppress the spread of the Covid-19 virus in the form of restrictions on outdoor activities is shown from the results of various studies to affect the increase in screen time and decrease in physical activity. The purpose of this study was to determine the relationship between screen time and physical activity in adolescents before, during, and after the Covid-19 pandemic. The method used was quantitative research with an observational study that was analytical and a cross-sectional approach. Data collection was carried out using a questionnaire on 135 adolescents, including students from SMAN 1 Mataram and SMAN 5 Mataram. The results of the statistical test of screen time with physical activity before, during, and after the pandemic were p = 0.430, p = 0.426, and p = 0.198, respectively. Therefore, in this study it can be concluded that there is no relationship between screen time and physical activity before, during, and after the Covid-19 pandemic.